Crustal deformation monitoring by the Kalman filter method - Çelik, Cahit Tăgi (1998)
The Earth's crust is deforming continuously due to plate tectonics. Deformation at plate boundaries causes volcanoes and most destructive earthquakes. Monitoring such deformation is essential to gaining an insight into the mechanisms of plate tectonics.